The diet and feeding habits of Lagocephalus sceleratus in the eastern Mediterranean: A case study carried out off the island of Crete (southern Greece) - GOMES V.C. , RITA; CHRISTIDIS, GEORGIOS; PERISTERAKI, PANAGIOTA; SOMARAKIS, STYLIANOS; TSERPES, GEORGE (Mediterranean Marine Science, 2025)
This study focused on the diet and feeding habits of the invasive pufferfish Lagocephalus sceleratus in the coastal waters of Crete (Cretan and Libyan Sea, eastern Mediterranean). The diet was composed of a wide variety of organisms, while the number of specimens with empty gastrointestinal tracts was low (14.41%). In total we were able to identify 38 different species of fish and invertebrates within the tracts analysed. Fish were the main diet component, followed by crustaceans and mollusks (mostly gastropods and cephalopods). At family level, the most significant preys were Sparidae and Mullidae teleosts, along with Cavoliniidae gastropods. The trophic level of L. sceleratus was estimated to be 4.13. The trophic niche breadth was intermediate, whereas the L. sceleratus population exhibits a mixed feeding strategy. Spatiotemporal differences in diet composition were also identified. The application of generalized additive models (GAMs) revealed that depth at which the fish were captured, season, region and total length, were significant predictors of the probability of occurrence of its most frequent prey groups. Fish prey occurrence was more probable in autumn and summer and at circa 20-25 m depth. In contrast, the probability of consuming crustaceans was higher in spring and winter and in specimens measuring 450-500 mm in length, and lower at 20-25 m, whilst increasing until a maximum at 40 m. The probability of non-cephalopod mollusks consumption was higher in winter and in the Libyan Sea, as well as at greater depths. Fish size had a significant effect on the likelihood of consuming photosynthetic organisms (algae and seagrass) and cephalopods, which was higher in larger fish. This study presents further evidence of the negative impact of L. sceleratus on the fisheries sector, revealing both predation on commercial species and the ingestion of various fishing gear parts.